Diseño de un sistema de costos en el Centro de Mecanización Unión y Trabajo, cantón Salcedo parroquia Mulalillo. - Yépez Orozco, Maricela Alexandra (2019)
The Union and Labor Mechanized Center manages the financial area in an empirical way, this is evidenced in the previous analysis, applied to the organization, which makes it difficult for the president to make decisions, it is for this reason and with the purpose to correct the ignorance of the elements of the cost and the real cost that is generated when rendering its agricultural machinery service, this integrating project, aims to design a cost system for production orders, which allows for efficient management and control of the economic resources of entrepreneurship Through the situational diagnosis, a clearer idea of the problem in question was obtained. To be able to fulfill the purpose in the present project, a quantitative approach of descriptive type was used, with tools of reelection of bibliographic and documentary information; research techniques, such as the interview application and observation sheet made to the administrator and the machinery operator respectively. All this with the objective of collecting primary information, necessary for the proposal of the cost system. In addition, the competences related to the professional field and the technical scientific foundation are described as an important contribution to the development of the project. At the end of the work, it was determined that at present, the Mechanized Center does not consider all the CIFs in which the service is incurred, where depreciation stands out in a greater percentage, in addition to the fact that the sale price is raised empirically , it is for this reason that the value per hectare once the cost system for production orders is applied increases, in the plow of $ 22.83 that is currently charged to $ 35.71 and the trace of $ 40.00 to $ 62 , 57, this is because depreciation is not included in its costs, nor is the cost generated by the acquisition of tires and lubricants, proposing that the cost system should be applied, with the purpose of generating utility and anticipating the replacement of fixed assets when they end their useful life.